1982
DOI: 10.1037/0096-3445.111.4.390
|View full text |Cite
|
Sign up to set email alerts
|

Differences in approaches to learning: An overview.

Abstract: This article provides an overview for three sets of experiments that examine differences in the way that academically successful and less successful fifth-grade students approach the problem of learning new information. The overview includes discussions of (a) theoretical approaches to the problem of learning new information, (b) pilot studies that suggest differences in successful and less successful students' approaches to learning, and (c) specific hypotheses about reasons for the differences in learning su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
0
5

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 40 publications
2
91
0
5
Order By: Relevance
“…Rather, explorations of the impact on acquisition of explicit knowledge through explanation provision in intelligent systems provide mixed evidence. Bransford et al (1982), Franks et al (1982), Stein et al (1982a), and Stein et al (1982b) found that the precision of an explanation embedded within an intelligent system positively affects the development of explicit knowledge. Intelligent system explanations embedded with explicit knowledge have been shown to successfully increase long-term memory storage of explicit knowledge (Smedley and Sutton 2004).…”
Section: Background and Theoretical Discussionmentioning
confidence: 99%
“…Rather, explorations of the impact on acquisition of explicit knowledge through explanation provision in intelligent systems provide mixed evidence. Bransford et al (1982), Franks et al (1982), Stein et al (1982a), and Stein et al (1982b) found that the precision of an explanation embedded within an intelligent system positively affects the development of explicit knowledge. Intelligent system explanations embedded with explicit knowledge have been shown to successfully increase long-term memory storage of explicit knowledge (Smedley and Sutton 2004).…”
Section: Background and Theoretical Discussionmentioning
confidence: 99%
“…, precise elaborations, following their terminology). Bransford and colleagues have conducted a number of studies (e.g., Bransford et al , 1982;Owings, Petersen, Bransford, Morris, & Stein, 1980;Stein, Littlefield, Bransford, & Persampieri, 1984) in which subjects (both children and adults) have been presented a series of mutually interfering sentences that specified relationships that arenot obviously meaningful at first glance (base sentences, again following the terminology employed in Bransford's publications) . For example, three base sentences used in these studies were the following:…”
Section: Some Elaborative Strategies Can Be Carried Out By Older But mentioning
confidence: 99%
“…These tasks can be difficult even for proficient adult learners (e.g. Bransford, Stein, Vye, Franks, Auble, Mezynski and Perfetto, 1982;Pressley, Symons, McDaniel, Snyder and Turnure, 1988), let alone children, who were studied in the investigation reported here. Although we do not agree with extreme arguments that even more fact learning should be presented in school (e.g.…”
mentioning
confidence: 99%